Performance assessment model for academic libraries: the Covenant University Library example (2016)
The study explores performance assessment models in academic libraries and show-cases the practical experiences at the Covenant University Library. The paper which is based on an observational study of the researchers’ daily work experiences and review of literature identified constraints to performance assessment in academic libraries and has attempted to give solutions. The paper concludes that academic libraries should overcome constraints and imbibe the culture of performance assessment that involves a continuous and periodic process of fine-tuning critical management and functional processes, either reactively or proactively through deliberately designed parameters (indicators). It extrapolated from the unique experiences of the Centre for Learning Resources, Covenant University to construct a model (Lib-PERFQUAL) for libraries around the world. This is a model that comprises all indicators necessary to maintain continuous relevance and achieve utmost efficiency.